2021
DOI: 10.3390/healthcare9060753
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Weight Loss in Adult Patients and the Effect of Staffing Registered Dietitians in Kaifukuki (Convalescent) Rehabilitation Wards: A Retrospective Analysis of a Nationwide Survey

Abstract: There is scarce evidence regarding the risk of weight loss and the effect of having registered dietitians (RDs) on staff in rehabilitation wards on weight loss. We aimed to examine the effects of RDs in Kaifukuki (convalescent) rehabilitation wards (KRWs) on the prevention of weight loss in adult patients. Data from 2-year nationwide annual surveys on KRWs in Japan were retrospectively analysed. Weight loss was defined as loss of ≥5% weight during the KRW stay. Risk of weight loss in class 1 KRWs (obligated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This retrospective multicenter cohort study was conducted in three hospitals (with 143–500 beds each) with convalescent rehabilitation wards and located in different prefectures in Japan: Hamamatsu City, Shizuoka; Daito City, Osaka; Nagasaki City, Nagasaki. All three hospitals included certified convalescent rehabilitation wards under public healthcare insurance policy in Japan [ 22 , 23 ]. Local investigators collected data for consecutive patients admitted to each hospital for post-stroke rehabilitation between 1 November 2018, and 31 October 2020.…”
Section: Methodsmentioning
confidence: 99%
“…This retrospective multicenter cohort study was conducted in three hospitals (with 143–500 beds each) with convalescent rehabilitation wards and located in different prefectures in Japan: Hamamatsu City, Shizuoka; Daito City, Osaka; Nagasaki City, Nagasaki. All three hospitals included certified convalescent rehabilitation wards under public healthcare insurance policy in Japan [ 22 , 23 ]. Local investigators collected data for consecutive patients admitted to each hospital for post-stroke rehabilitation between 1 November 2018, and 31 October 2020.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review, which included a study conducted in rehabilitation facilities in Singapore, showed that dysphagia was associated with malnutrition [41]. Additionally, onset-admission interval can be associated with a risk of weight loss in patients in convalescent rehabilitation wards [49]. Regarding sarcopenia, older age and limited mobility were independently associated with decreased muscle mass in hospitalised older adults in Japan [50].…”
Section: Potentially Associated Factors Of the Co-msmentioning
confidence: 99%